2011
DOI: 10.1016/j.surg.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of citrullinated histone H3 as a potential serum protein biomarker in a lethal model of lipopolysaccharide-induced shock

Abstract: Background Circulating proteins may serve as biomarkers for the early diagnosis and treatment of shock. We have recently demonstrated that treatment with suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor, significantly improves survival in a rodent model of lipopolysaccharide (LPS)-induced septic shock. Preliminary proteomic data showed that LPS-induced shock altered a number of proteins in circulation, including histone H3 (H3) and citrullinated histone H3 (Cit H3). The present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 20 publications
5
83
2
Order By: Relevance
“…Furthermore, supplemental Figure 3C shows histone release and fragmentation over time, similarly to that reported by Xu et al 9 Although necrotic cells also release nucleosomes in endotoxemia, 45 we saw that with increasing DNA release over time, H3Cit, a NET biomarker, became detectable in the plasma of PAD4 1/1 mice (supplemental Figure 3D), as was previously shown using low and high doses of LPS, 43 indicating that NETs are formed in our model. To investigate the effect of NETs in the LPS model, we compared PAD4 2/2 to PAD4 1/1 mice.…”
Section: Pad4supporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, supplemental Figure 3C shows histone release and fragmentation over time, similarly to that reported by Xu et al 9 Although necrotic cells also release nucleosomes in endotoxemia, 45 we saw that with increasing DNA release over time, H3Cit, a NET biomarker, became detectable in the plasma of PAD4 1/1 mice (supplemental Figure 3D), as was previously shown using low and high doses of LPS, 43 indicating that NETs are formed in our model. To investigate the effect of NETs in the LPS model, we compared PAD4 2/2 to PAD4 1/1 mice.…”
Section: Pad4supporting
confidence: 89%
“…9,35 In vivo, histones contribute substantially to mortality in sepsis 9 and can induce thrombocytopenia. 42 In order to study the effect of NETs and endotoxemia in mice without a live bacterial infection, we turned to established models of LPS-induced shock 9,43 to generate large amounts of circulating nucleosomes in vivo. While not an ideal model of human sepsis, LPS infusion allowed us to investigate the host response leading to endotoxemic shock, which has been extensively studied experimentally.…”
Section: Pad4mentioning
confidence: 99%
“…This observation supports the idea that citrullination of histone H3 is mandatory for the process of NETosis before nuclear decondensation. A previous report suggested that Cit H3 is released into the circulation during the early stage of lipopolysaccharide-induced shock and it is associated with the severity of shock in a mouse model [20]. Our data suggests that the quantity of Cit H3 has potential as a clinical biomarker of the severity of infection, independent from other well-known inflammatory biomarkers such as C-reactive protein and PCT.…”
Section: Discussionsupporting
confidence: 57%
“…This phenotype was abolished after neutrophil depletion and exogenous administration of DNAse 1 and NEi, implicating NETs as the likely source of extracellular DNA. The finding of widespread NET deposition following CLP is not unexpected, and extensive data in the literature exists that describes NET formation in vivo in the context of sepsis (48,59,60).…”
Section: Figurementioning
confidence: 91%